1981
DOI: 10.1021/jm00144a019
|View full text |Cite
|
Sign up to set email alerts
|

2,3-Dihydrobenzofuran-2-ones: a new class of highly potent antiinflammatory agents

Abstract: A series of 2,3-dihydrobenzofuran-2-one analogues of the mold metabolite wortmannin, which is a powerful antiinflammatory compound, was synthesized. Most of these compounds were tested for their ability to inhibit the carrageenin paw edema and the adjuvant-induced arthritis of the rat and for their ability to inhibit prostaglandin synthesis in vitro. Indomethacin and diclofenac were used as references. The results show that compounds bearing an alkyl or aryl group in position 6 and an additional substituent, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 5 publications
(8 reference statements)
2
15
0
Order By: Relevance
“…Purification of the residue by column chromatography (cyclohexane/CH 2 Cl 2 2:8) and recrystallization gave the desired product as white crystals. Yield: 89 % (0.267 g); mp: 48 °C (Et 2 O/petroleum ether); 1 H NMR and IR spectra are in accord with published data 55…”
Section: Methodssupporting
confidence: 79%
“…Purification of the residue by column chromatography (cyclohexane/CH 2 Cl 2 2:8) and recrystallization gave the desired product as white crystals. Yield: 89 % (0.267 g); mp: 48 °C (Et 2 O/petroleum ether); 1 H NMR and IR spectra are in accord with published data 55…”
Section: Methodssupporting
confidence: 79%
“…2,3±Dihydrobenzofuran-2-one derivatives are of great interest because of their biological properties. Some derivatives of 2,3dihydrobenzofuran-2-one have been reported as potential inhibitors of angiogensis (Du¯os et al, 2003) and as drugs for the treatment of hypoxia (Lepagnol & Lavielle, 1988) and some also show high ef®cacy as intrinsic analgesics and anti-in¯ammatories (Baumann et al, 1986, Rao & Rau, 1985, Closse et al, 1981. We report here the crystal structure of the title compound, (I).…”
Section: Commentmentioning
confidence: 83%
“…2,3-Dihydrobenzofurans have been known as potent anti-inflammatory compounds. Closse et al [ 17 ] demonstrated that the synthetic analogues of 2,3-dihydrobenzofuran-2-one had powerful anti-inflammatory activity in vivo, and 5-chloro-6-cyclohexyl-2,3-dihydrobenzofuran-2-one was significantly more potent than the reference compound, diclofenac, in all testing models. More recently, a series of dihydrobenzofurans was isolated from the seeds of Prunus tomentosa , some of which strongly inhibited NO production in LPS-stimulated BV-2 cells [ 18 ].…”
Section: Resultsmentioning
confidence: 99%